Peran Holistic Health Care Terhadap Kualitas Hidup Pasien Stroke: Literatur Review - Hernani, Eny; Sagiran, Sagiran (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Â The word health service has trying to apply holistic has concept that sees people wholy, consisting of thought, not balanced emotion, physics, social, spiritual and environment. Holistic Health Care (HHC) is a trial to remedy patients which focuses onpsychological and spiritual aspect of the patients besides medical or physical aspect the increasing of prevalentcronic illness or onspread illness becomes national or global health problems now. One of them is stroke illness, the highest cause of death and disability in Indonesia is stroke illness. It is suffered by people over 45 years old, globaly the death it is 87% caused by stroke illness, stroke illness causes the patient feels changing on his heart, social role, self-care, and dropping work product. So stroke patient needs scale measurement of life quality.Methods: The method which is applied in this reseach (paper) literature of review study. It is adopted from PubMed, ProQuest, Ebsco Host with their key words holistic nursing care or holistic health and quality of life And stroke , and the years has the range of time between 2015 to 2019.Results: Based on this research through datebase PubMed, ProQuest, Ebsco Host, cause we got 7 articles which support the tittle we got 7 articles which two of them talk about holistic, one of them talks about spirituality, and four of them talk about alive quality of stroke patients.Conclusion: The application of holistic health care in the hospital and increasing the life quality of the patient better than stroke patients.